Empowering Character Building through “DARLING Community” in Primary Education - Wulandari, Rifa Suci (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
Good character is not formed automatically; it is developed over time through a sustained process of teaching. Character education is a national movement to foster ethical, responsible and caring young people by modeling and teaching good character through emphasis on universal values. Religiosity, honesty, responsibility, healthy lifestyle, discipline, hard work, confidence, entrepreneurship, logical, critical, creativity, innovative thinking, independence, curiosity, joyfulness of reading, cooperativeness, obedience, respect, courtesy, democratic, environmental care, nationalism, and respect for diversity are the values that can be taught at school. The proactive effort by schools to instill in the important universal values can be done either in curricular or extracurricular activities. One of the  strategies to integrate character building is ‘DARLING community”.. Having characters which signifies awareness to environmental problems and ability to protect the environment is as important as having desirable characters that can help students to succeed in live. This article provides the guidelines for effective and comprehensive character education and discussion about the characters building within environmental education and some proposed models to integrate environmental education into teaching in primary education